2006
DOI: 10.1021/ac061090e
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Detection of Kinetic Germination and Heterogeneity of Single Bacillus Spores by Laser Tweezers Raman Spectroscopy

Abstract: Germination is the process by which a dormant spore returns to its vegetative state when exposed to suitable conditions. We report on the real-time detection of kinetic germination and heterogeneity of single Bacillus thuringiensis spores in an aqueous solution by monitoring the calcium dipicolinate (CaDPA) biomarker with laser tweezers Raman spectroscopy (LTRS). A single B. thuringiensis spore was optically trapped in a focused laser beam, and its Raman spectra were recorded sequentially in time after exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
149
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(156 citation statements)
references
References 29 publications
7
149
0
Order By: Relevance
“…A number of studies have shown that Raman scattering-based methods allow for the assessment of the type of contamination, as well as the degree of contamination in such applications. [79][80][81][82][83][84] In early work, Choo-Smith et al 85 86 used Raman spectroscopy to quantify filtered waterborne pathogenic microbial contamination, and Pasteris et al 87 used Raman spectroscopy to identify sulfur inclusions in sulfur-oxidizing marine bacteria. Recently, Palchaudhuri et al 88 investigated the uptake and metabolism of the five-carbon sugar alcohol xylitol by gram-positive viridian group Streptococcus and two gram-negative Escherichia coli strains.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…A number of studies have shown that Raman scattering-based methods allow for the assessment of the type of contamination, as well as the degree of contamination in such applications. [79][80][81][82][83][84] In early work, Choo-Smith et al 85 86 used Raman spectroscopy to quantify filtered waterborne pathogenic microbial contamination, and Pasteris et al 87 used Raman spectroscopy to identify sulfur inclusions in sulfur-oxidizing marine bacteria. Recently, Palchaudhuri et al 88 investigated the uptake and metabolism of the five-carbon sugar alcohol xylitol by gram-positive viridian group Streptococcus and two gram-negative Escherichia coli strains.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…While Ca-DPA solubility is ϳ70 mM, the Ca-DPA concentration in total dormant spore water would be ϳ90 mM if all were soluble, assuming the weight of a B. subtilis spore is 6 ϫ 10 Ϫ13 g, contains 10% dry weight as DPA, and is ϳ70% water (17,28). However, full release of Ca-DPA from the core during germination takes 1 to 3 min for an individual spore (4,13,22,35), indicating that there is ample time for tremendous dilution of this released Ca-DPA well before an adjacent spore is encountered. Consequently, it is perhaps not unexpected that Ca-DPA released from one spore is not especially effective in triggering the germination of an adjacent spore.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the rates of germination of individual spores are extremely heterogeneous due to the variations in t lag (4,11,13,35). Some of the factors that influence t lag values have recently been elucidated (35), although there could well be additional important factors.…”
mentioning
confidence: 99%
See 2 more Smart Citations